COVID-19 in cancer patients: managing a pandemic within a pandemic. - Figueira, Karina (2020)
The 2019 coronavirus disease pandemic (COVID-19) has disrupted health care worldwide. Cancer patients appear to be particularly susceptible to the morbidity and mortality of this new disease. No specific therapy for COVID-19 currently appears to offer a survival benefit for this patient population. In addition, the global effects on routine cancer treatment are likely to be felt only in the coming decades.